2023
DOI: 10.1038/s41392-022-01297-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for head and neck cancer: signaling pathways and clinical studies

Abstract: Head and neck cancer (HNC) is malignant, genetically complex and difficult to treat and is the sixth most frequent cancer, with tobacco, alcohol and human papillomavirus being major risk factors. Based on epigenetic data, HNC is remarkably heterogeneous, and treatment remains challenging. There is a lack of significant improvement in survival and quality of life in patients with HNC. Over half of HNC patients experience locoregional recurrence or distal metastasis despite the current multiple traditional thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 520 publications
0
31
0
Order By: Relevance
“…Over the past few decades, the advent of molecular‐targeted therapy has yielded significant clinical advancements in the management of HNSC. Regrettably, a majority of patients inevitably develop resistance to these targeted interventions, thereby perpetuating a bleak prognosis 2–5 . The utilization of immune checkpoint inhibitors (ICIs) has emerged as a novel therapeutic approach in the management of HNSCs 6–9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, the advent of molecular‐targeted therapy has yielded significant clinical advancements in the management of HNSC. Regrettably, a majority of patients inevitably develop resistance to these targeted interventions, thereby perpetuating a bleak prognosis 2–5 . The utilization of immune checkpoint inhibitors (ICIs) has emerged as a novel therapeutic approach in the management of HNSCs 6–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, a majority of patients inevitably develop resistance to these targeted interventions, thereby perpetuating a bleak prognosis. [2][3][4][5] The utilization of immune checkpoint inhibitors (ICIs) has emerged as a novel therapeutic approach in the management of HNSCs. [6][7][8][9] Regrettably, the overall response rates and efficacy remain suboptimal, primarily because of the inherent "cold" nature of HNSCs characterized by an immunosuppressive tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer is the sixth most common cancer globally and has become a global health concern 1 . Various treatment modalities are recommended for cancer patients, such as surgery, radiation therapy, chemotherapy, or a combination thereof, and long‐term follow‐up 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer is the sixth most common cancer globally and has become a global health concern. 1 Various treatment modalities are recommended for cancer patients, such as surgery, radiation therapy, chemotherapy, or a combination thereof, and long-term follow-up. 2 Chemotherapy and radiation therapy are nonsurgical methods used today to treat head and neck cancers, prolong survival rates, or completely cure the mass.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, several studies have reported an inverse correlation between high EGFR copy number or overexpression and HPV status. 13 Preclinical studies reported that loss of EGFR 14,15 or TGFa 16 expression using genetic means (eg, antisense strategy or silent RNA knockdown) or therapeutic inhibition of EGFR 17,18 decreased the proliferation of HNSCC cells in vitro and in patient-derived xenografts in mouse models. 19 However, the effects were often modest as monotherapy but were enhanced when combined with another treatment such as chemotherapy 15 or radiotherapy, as shown for example in combination with cetuximab.…”
mentioning
confidence: 99%